2018
DOI: 10.4014/jmb.1808.08001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Lytic and Highly Specific Phage against Yersinia enterocolitica as a Novel Biocontrol Agent

Abstract: Yersinia enterocolitica is a gram-negative, non-spore-forming, coccobacilli, psychrotrophic, and facultative anaerobe, which is one of three Yersinia species that are pathogenic to humans, along with Y. pestis, and Y. pseudotuberculosis [1, 2]. The most predominant natural hosts for Y. enterocolitica are animals (especially pigs). Y. enterocolitica also exists ubiquitously in water, soil, plant surfaces, and foods [3]. Although animals are the major source of Y. enterocolitica, many cases have recently been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The room temperature accelerated the reduction of the phage cocktail concentration more than cold temperature in this study. The other study [28] also confirmed the lower feasibility of Yersinia enterocolitica-specific phage when exposed to room temperature rather than deep freezing, freezing, and cold temperatures. In fact, most of the several commercial phage cocktails approved by the FDA were sold under cold storage conditions (2℃-8℃) [30].…”
Section: Storage Stability Of Kfs-stsupporting
confidence: 57%
See 1 more Smart Citation
“…The room temperature accelerated the reduction of the phage cocktail concentration more than cold temperature in this study. The other study [28] also confirmed the lower feasibility of Yersinia enterocolitica-specific phage when exposed to room temperature rather than deep freezing, freezing, and cold temperatures. In fact, most of the several commercial phage cocktails approved by the FDA were sold under cold storage conditions (2℃-8℃) [30].…”
Section: Storage Stability Of Kfs-stsupporting
confidence: 57%
“…Antibodies are the most popularly employed bio-receptor, however, their most considerable limitations include their need for storage at cold temperatures and their average shelf life of one month [27]. By contrast phage possess excellent stability at relatively broad temperature ranges during long periods [28]. Thus, the influence of storage period and temperature were investigated by measuring the concentration of KFS-ST after exposure to various storage conditions over a period of 12 weeks (Table 3).…”
Section: Storage Stability Of Kfs-stmentioning
confidence: 99%
“…Phages have been increasingly investigated as specific, natural, eco-friendly, and promising biocontrol agents against foodborne pathogens [20]. In particular, their ubiquitous existence in nature (10 31 phages) and excellent target-dependent specificity have provided extensive investigation of phage from various sources such as sewage, human and animal feces, and foods [21]. Moreover, the unique characteristics of the phage life cycle, either lytic or lysogenic (temperate), are usually investigated for phage application [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the sensitivity of phage ZCSE6 toward temperature, there was a reduction in phage titer after incubating the phage at −20 • C due to the formation of ice crystals, thus the glycerol is preferred to be added to keep the phages safe at temperatures lower than 0 • C [34]. Furthermore, the thermal stability of phage ZCSE6 to a wide range of temperatures ranging from −20 • C to 70 • C was confirmed.…”
Section: Discussionmentioning
confidence: 78%